Changes in Global Blocking Character in Recent Decades - Anthony R. Lupo; Andrew D. Jensen; Igor I. Mokhov; Alexander V. Timazhev; Timothy Eichler; Bahtiyar Efe (Atmosphere, 2019)
A global blocking climatology published by this group for events that occurred during the late 20th century examined a comprehensive list of characteristics that included block intensity (BI). In addition to confirming the results of other published climatologies, they found that Northern Hemisphere (NH) blocking events (1968–1998) were stronger than Southern Hemisphere (SH) blocks and winter events are stronger than summer events in both hemispheres. This work also examined the interannual variability of blocking as related to El Niño and Southern Oscillation (ENSO). Since the late 20th century, there is evidence that the occurrence of blocking has increased globally. A comparison of blocking characteristics since 1998 (1998–2018 NH; 2000–2018 SH) shows that the number of blocking events and their duration have increased significantly in both hemispheres. The blocking BI has decreased by about six percent in the NH, but there was little change in the BI for the SH events. Additionally, there is little or no change in the primary genesis regions of blocking. An examination of variability related to ENSO reveals that the NH interannual-scale variations found in the earlier work has reversed in the early 21st century. This could either be the result of interdecadal variability or a change in the climate. Interdecadal variations are examined as well.